Atropisomerism in 3, 4, 5‐Tri‐(2‐methoxyphenyl)‐2, 6‐lutidine. Issue 35 (12th November 2013) - Roszkowski, Piotr; Błachut, Dariusz; Maurin, Jan K.; Woźnica, Magdalena; Frelek, Jadwiga; Pluciński, Franciszek; Czarnocki, Zbigniew
Abstract: Suzuki reaction of tribromo‐2, 6‐lutidine with (2‐methoxyphenyl)boronic acid gave 3, 4, 5‐tris(2‐methoxyphenyl)‐2, 6‐lutidine in the form of a mixture of three atropisomers that were stable at room temperature. Each isomer was isolated and fully characterized, including by X‐ray structure determination. One of the isomers, being a racemic mixture, was separated into individual enantiomers by using semipreparative chiral HPLC. Their absolute stereochemistry was initially assigned on the basis of computational calculation of the CD spectra and finally confirmed by X‐ray analysis. Abstract : Arylation of tribromo‐2, 6‐lutidine with (2‐methoxyphenyl)boronic acid gave 3, 4, 5‐tris(2‐methoxyphenyl)‐2, 6‐lutidine in the form of a mixture of three atropisomers7a –c, which were stable at room temperature. Their absolute stereochemistry was assigned, and their thermal interconversion was studied.